Challenges to Local Public Service in the Post Pandemic - Satwika Wijaya, Shadu; Rosyadi, Slamet; ., Simin; Gunarto, Guntur; ., Anwarudin (KnE Social Sciences, 2023)
The relevance of the New Public Administration (NPA) Paradigm initiated by Frederickson shows its increasing power. Although this paradigm appeared far before the change in global post-pandemic conditions, the New Public Administration (NPA) Paradigm is capable of guiding the public administrative measures to respond to the challenge of post-pandemic social change, especially in the public service administration aspect. Public service before the pandemic, especially at the local government level, had found form and quality issues. The public service at the local level is attempting to respond to public needs and social changes that are always a big challenge for public administration. The pandemic suddenly worsened and was a blow to the process of public administration adjustment to the changes. The public service that needed modernization was badly hit by the pandemic. Therefore, this article aims to identify challenges to public administration in the context of post-pandemic changes in public service. This research used a focus group discussion method with stakeholders and documentation as the secondary data. This article successfully shows the important position of amplification of changes and responsiveness in public administration, especially in public service delivery. Keywords: new public administration, public service delivery, policy change, post-pandemic era, responsiveness